Análisis de las ventas de la Empresa Marecillo S.A. a causa de la pandemia y su efecto en las futuras inversiones - Cabrera Garcia, Miguel Angel (2020)
The project Analysis of the sales of the company marecillo s.a. Due to the pandemic and its effect on future investments, its objective is to analyze the economic situation of the shrimp sector of the Machala canton of the company Marecillo S.A. The study process, a descriptive analytical investigation was carried out. The importance of this research is based on the development of aquaculture, being one of the countries with the greatest influence in the shrimp sector today due to its development in aquaculture as it handles perfect climatic factors allowing a large production without major inconveniences. generating, each time, a favorable increase inside and outside the country in the economic sphere, increasing trust and credibility with the quality of its products.Finally, the accounting statements are reflected to evaluate the financial and operational performance together with certain indicators in the economy to world level which influence as main resources in the source of income that allows the company in the periods 2019 - 2020 to the managers a better understanding of the economic situation, in order to make decisions that allow them to progress their economy with plans investment appropriate for its development.